Epidemiology of Antibiotic and Heavy Metal Resistance in Bacteria: Resistance Patterns in Staphylococci Isolated from Populations in Iraq Exposed and Not Exposed to Heavy Metals or Antibiotics - Groves, David J. (1975)
Staphylococci were isolated from rural and urban populations in Iraq, which were not known to be exposed to either heavy metals or antibiotics. The antibiotic and heavy metal resistance patterns of these strains were analyzed in both mannitol-fermenting and nonfermenting strains. Over 90% of the strains were resistant to at least one of the following antibiotics: penicillin, chloramphenicol, erythromycin, tetracycline, cephalothin, lincomycin, or methicillin. In general, mannitol-fermenting strains were resistant to penicillin and cupric ions. Mannitol-negative strains were more frequently associated with mercuric ion and tetracycline resistance. Although resistance to penicillin and tetracycline can coexist, the combination of penicillin resistance and tetracycline resistance usually occurred in mannitol-negative strains. The possibility of selection of heavy metal-resistant strains due to exposure to toxic levels of methylmercury was examined. No significant increase in mercuric ion-resistant strains of staphylococci or Escherichia coli were detected in exposed populations as compared to control groups. The possible reasons for this result are discussed.